Gas Bubble Disease in the Brain of a Living California Sea Lion (Zalophus californianus) - Van Bonn, William G.; Dennison, Sophie; Cook, Peter; Fahlman, Andreas (Frontiers in Physiology, 2013)
A yearling California sea lion (Zalophus californianus) was admitted into rehabilitation with signs of cerebellar pathology. Diagnostic imaging that included radiography and magnetic resonance imaging (MRI) demonstrated space-occupying lesions predominantly in the cerebellum that were filled partially by CSF-like fluid and partially by gas, and cerebral lesions that were fluid filled. Over a maximum period of four months, the brain lesions reduced in size and the gas resorbed and was replaced by CSF-like fluid. To test the animal in this study for motor memory deficits, an alternation task in a two-choice maze was utilized. The sea lion performed poorly similar to another case of pneumocerebellum previously reported, and contrary to data acquired from a group of sea lions with specific hippocampal injury. The learning deficits were attributed to the cerebellar injury. These data provide important insight both to the clinical presentation and behavioral observations of cerebellar injury in sea lions, as well as providing an initial model for long-term outcome following cerebellar injury. The specific etiology of the gas could not be determined. The live status of the patient with recovery suggests that the most likely etiologies for the gas are either de novo formation or air emboli secondary to trauma. A small air gun pellet was present within and was removed from soft tissues adjacent to the tympanic bulla. While no evidence to support the pellet striking bone was found, altered dive pattern associated with this human interaction may have provided the opportunity for gas bubble formation to occur. The similarity in distribution of the gas bubble related lesions in this case compared with another previously published case of pneumocerebellum suggests that preferential perfusion of the brain, and more specifically the cerebellum, may occur during diving events.